The TEI and Current Standards for Structuring Linguistic Data - Maik Stührenberg (Journal of the Text Encoding Initiative)
The TEI has served for many years as a mature annotation format for corpora of different types, including linguistically annotated data. Although it is based on the consensus of a large community, it does not have the legal status of a standard. During the last decade, efforts have been undertaken to develop definitive de jure standards for linguistic data that not only act as a normative basis for the exchange of language corpora but also address recent advancements in technology, such as web-based standards, and the use of large and multiply annotated corpora. In this article we will provide an overview of the process of international standardization and discuss some of the international standards currently being developed under the auspices of ISO/TC 37, a technical committee called “Terminology and other Language and Content Resources”. After that the relationship between the TEI Guidelines and these specifications, according to their formal model, notation format, and annotation model, will be discussed. The conclusion of the paper provides recommendations for dealing with language corpora.